Impact of adolescent identity construction on the establishment of dysfunctional behaviors and on the generation of coping strategies. (European Journal of Child Development, Education and Psychopathology, 2019)
Despite its importance in the human life cycle, little literature has been found about how the development of identity influences the appearance of dysfunctional behaviors and coping strategies in adolescence. The objective of present study is to detect whether identity development influences the generation of problematic or protective behaviors in adolescence; and the weight of certain individual characteristics in this interaction. We evaluated 36 adolescents with a test battery designed for the present study. The data were analyzed statistically with correlation models and multiple linear regression. It was found that identity development is a factor that influences the generation of both problematic and protective behaviors. Likewise, both types of behaviors were good predictors of each other. Self-concept and personality also influence; to the point of being more explanatory than the identity. The Dweck scale was discarded as an intermediary factor in these relationships. In conclusion, identity influences the generation of problematic and protective behaviors; but other factors were to be more explanatory. The results suggest that during the adolescence, period of transition and change, the content of own impressions or personality traits prevails to define the person, rather than the identity maturity.